Governance and the conditional effects of external debt on economic growth: Evidence from developing economies using CS-ARDL - Tarchoun, Monaem; Ghraieb, Ikram (International Journal of Innovative Research and Scientific Studies, 2025)
This research examines the effect of external debt on economic growth in developing countries, with a focus on the role of institutional quality as a moderating variable. A panel dataset of 20 developing countries from 1990 to 2023 is utilized alongside the Cross-Sectionally Augmented Autoregressive Distributed Lag (CS-ARDL) methodology. to control for cross-sectional dependence, heterogeneity, as well as both short-run and long-run dynamics. The results confirm and retain the potential for long-run relationships between the variables. The empirical evidence shows that external debt negatively impacts economic growth in countries with weak institutions, indicative of the debt overhang hypothesis. By contrast, strong institutions reduce the negative impact of debt, while enhancing the positive effect of debt on growth. Trade openness, foreign direct investment, and financial development positively affect economic growth, while inflation negatively impacts it. The findings indicate that governance is essential when crafting policy around debt, hence, careful borrowing, guided by strong institutional quality, can turn external debt into a source of sustainable economic growth. As for policy implications, engaged institutions are needed, debt needs to be made visible, debt needs to be prioritized towards productive investment and macroeconomic stability also needs to be retained.